Dynamic Fixation vs Static Screw Fixation for Syndesmosis Injuries in Pronation External Rotation Ankle Fractures - Hyunseong Kang MD, PhD; Chaemoon Lim MD; Sungwook Choi MD, PhD (Foot & Ankle Orthopaedics)
Category: Trauma; Ankle Introduction/Purpose: The current standard treatment for ankle syndesmosis injury is static screw fixation. Dynamic fixation was developed to restore the dynamic function of the syndesmosis. The purpose of this study was to determine that which of static screw fixation and dynamic fixation is better for treatment of ankle syndesmosis injury in pronation external rotation fractures. Methods: 30 patients were treated with dynamic fixation (DF group) and 28 patients with static screw fixation (SF group). The primary outcome was Olerud–Molander Ankle Outcome Score. The secondary outcome were Visual Analogue Scale score and American Orthopedic Foot and Ankle Society score, radiographic outcomes, complications and cost effectiveness. To evaluate the radiographic outcome, the tibiofibular clear space, tibiofibular overlap, and medial clear space were compared using the pre-operative and last follow-up plain radiographs. To evaluate the cost effectiveness, the total hospital cost was compared between the two groups. Results: There was no significant difference in primary outcome. Moreover, there were no significant difference in secondary outcome, including Visual Analogue Scale score and American Orthopedic Foot and Ankle Society score and radiographic outcome. Two cases of reduction loss and four cases of screw breakage were observed in the SF group. No complication in the DF group was observed. Dynamic fixation was more cost effective than static screw fixation with respect to the total hospital cost Conclusion: Although dynamic fixation provided similar clinical and radiologic outcome, dynamic fixation is more cost effective with fewer complications than static screw fixation in ankle syndesmosis injury of pronation-external rotation fractures.